Response - Vollaard, N. B. J.; Metcalfe, R. S.; Williams, S. (Medicine & Science in Sports & Exercise, 2017)
Response of the authors to the letter to the editor (Verney J, Duclos M, Thivel D. Sprint interval training: what are the clinical implications and precautions? Med Sci Sports Exerc. 2017;49(11):2361-2) concerning Vollaard NB, Metcalfe RS, Williams S. Effect of number of sprints in an SIT session on change in V·O2max: a meta-analysis. Med Sci Sports Exerc. 2017;49(6):1147-56.